2022
DOI: 10.1002/hpm.3557
|View full text |Cite
|
Sign up to set email alerts
|

Exploring heterogeneity of national health insurance scheme enrolment among persons in the informal sector

Abstract: The Ghanaian government began implementing the National Health Insurance Scheme (NHIS) in 2005, anchored on the universal health coverage principle. However, informal sector workers contribute to the low enrolment into the scheme. This paper examines the factors that influence enrolment status in Ghana's NHIS among individuals in the informal sector. The study employed the fixed-effects logit model, using the Ghana Socioeconomic Panel Survey datasets. The findings revealed that gender, age, education, marital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
4
0
0
Order By: Relevance
“…Understandably, persons with basic level of education; the males; minority ethnic groups and persons who use pharmacy as their usual source of healthcare are less likely to enrol and stay active in the NHIS. These findings largely corroborate other studies conducted in Ghana [41,53,59,62,63] and elsewhere [4,5].…”
Section: Discussionsupporting
confidence: 91%
“…Understandably, persons with basic level of education; the males; minority ethnic groups and persons who use pharmacy as their usual source of healthcare are less likely to enrol and stay active in the NHIS. These findings largely corroborate other studies conducted in Ghana [41,53,59,62,63] and elsewhere [4,5].…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that rural residents suffering from fever, cold/cough, or diarrhoea exhibit a higher probability of visiting a modern healthcare facility compared to other illnesses. This result is consistent with the findings of Sekyi and Domanban (2012) in Ghana.…”
Section: Modern Healthseeking Behaviourssupporting
confidence: 93%
“…The estimated marginal effects suggest that individuals who suffer from either fever, cold/cough or diarrhoea were 24.1%, 19.3 and 26.7%, respectively, more likely to visit a health facility relative to other illnesses. This result is in line with the work of Sekyi and Domanban (2012). However, in a study in Zambia, Masiye and Kaonga (2016) found that having a headache, diarrhoea, or “other disease” was related to a lower likelihood of seeking formal treatment than reporting malaria or fever.…”
Section: Resultssupporting
confidence: 77%